A Survey From 1G to 5G Including the Advent of 6G: Architectures, Multiple Access Techniques, and Emerging Technologies - Shah, A. F. M. Shahen (IEEE, 2022)
There is an evolution in cellular communication due to the high demand for better quality of service, data rates, capacity, and lower latency. To satisfy these expectations, cellular network design is being drastically improved. This paper provides a survey of cellular network architectures, multiple access techniques, and emerging technologies from first generation (1G) to fifth generation (5G). The paper also includes a glimpse at what the forthcoming sixth generation (6G) might anticipate. The architecture of the cellular network from 1G to 5G is presented. Some of the important emerging technologies that enable the architecture to be improved and fulfill user needs are discussed. These emerging technologies include massive MIMO, software-defined networking, mm-Wave, etc. Moreover, multiple access techniques used from 1G to 5G are studied. Comparison among different generations of cellular communication is presented. There are challenges and open issues for 6G which are described.
Keywords: 5G; 6G; cellular network architectures; emerging technologies; massive MIMO; mm-Wave; multiple access techniques; software-defined networking; PERFORMANCE; NETWORKS; REALITY; Computer Science; Telecommunications